Periodontal pathogens are a risk factor of oral cavity squamous cell carcinoma, independent of tobacco and alcohol and human papillomavirus. Issue 3 (19th February 2019) - Ganly, Ian; Yang, Liying; Giese, Rachel A.; Hao, Yuhan; Nossa, Carlos W.; Morris, Luc G.T.; Rosenthal, Matthew; Migliacci, Jocelyn; Kelly, Dervla; Tseng, Wenzhi; Hu, Jiyuan; Li, Huilin; et al.
Abstract : Over the past decade, there has been a change in the epidemiology of oral cavity squamous cell cancer (OC‐SCC). Many new cases of OC‐SCC lack the recognized risk factors of smoking, alcohol and human papilloma virus. The aim of this study was to determine if the oral microbiome may be associated with OC‐SCC in nonsmoking HPV negative patients. We compared the oral microbiome of HPV‐negative nonsmoker OC‐SCC(n = 18), premalignant lesions(PML) (n = 8) and normal control patients (n = 12). Their oral microbiome was sampled by oral wash and defined by 16S rRNA gene sequencing. We report that the periodontal pathogens Fusobacterium, Prevotella, Alloprevotella were enriched while commensal Streptococcus depleted in OC‐SCC. Based on the four genera plus a marker genus Veillonella for PML, we classified the oral microbiome into two types. Gene/pathway analysis revealed a progressive increase of genes encoding HSP90 and ligands for TLRs 1, 2 and 4 along the controls→PML → OC‐SCC progression sequence. Our findings suggest an association between periodontal pathogens and OC‐SCC in non smoking HPV negative patients. Abstract : What's new? Many recent cases of oral‐cavity squamous‐cell cancer (OC‐SCC) lack known risk factors such as smoking or HPV infection. In this study, the authors found that the oral microbiome of patients with OC‐SCC differed from normal controls. They also found that periodontal pathogens may contribute to the development of oral cancer by increasing inflammation, via increased expression of HSP90 and TLR ligands. These results have important public‐health implications for more efficient screening and early detection of OCSCC. Such patients might even be treated with antibiotics or probiotic agents to prevent further cancer progression.